The Roles of Epidemiologists, Laboratorians, and Public Health Agencies in Preventing Invasive Cronobacter Infection - Jason, Janine (Frontiers in Pediatrics, 2015)
Background: Cronobacter can cause severe, invasive infection in very young infants. These bacteria can also colonize or cause insignificant infections in immunocompromised, elderly, and/or hospitalized adults. Methods: This editorial review highlights key points addressed in the Frontiers Research Topic on Cronobacter, discusses the clinical presentation and epidemiology of Cronobacter infections, and examines the responses of public health agencies to this problem. Results: Cronobacter is rarely isolated from hospitalized, immunocompromised and/or elderly adults but does not cause significant disease in those patients. Certain species and strains, especially of C. sakazakii, can cause invasive illness in previously healthy infants less than two months of age. Multilocus sequence type 4 (ST4/MLST 4) and clonal complex 4 C. sakazakii are the predominant cause of Cronobacter meningitis, which occurs only in infants. These infections and this strain type are strongly linked to powdered infant formulas (PIF), which can also be contaminated with other Cronobacter strains. End-product testing does not and is not intended to guarantee the absence of these organisms. WHO has made recommendations that can help decrease but will not eliminate the risk of this infection. Conclusions: To further define the spectrum of Cronobacter-associated disease, all isolates should be genetically typed using every currently available method, typing results should be linked to the associated epidemiologic and clinical data, and these data should be analyzed in a scientifically sound manner. Based on currently available information, more can be done now to prevent cause invasive infection in young infants. This includes encouragement of exclusive breastfeeding and/or use of commercially sterile ready-to-feed formulas in the first two months of life.